The Effect of Transformational Leadership on Barista’s Innovative work behavior in Malang City - Mustikawati, Inka; Nurmala, Sukma (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Brawijaya, 2021)
This study was conducted to determine the effect of transformational leadership on innovative work behavior in baristas in the city of Malang. Respondents in this study were 126 baristas in Malang City (71 males and 55 females). This study uses a quantitative method with two scales, namely the Indonesian version of the transformational leadership scale which refers to the MLQ (Multifactor Leadership Questionnaire) Form 6s developed by Bass & Avolio (1992) and the individual innovative behavior scale which has been adapted by Nurmala & Widyasari (2021). ) which refers to the dimensions of innovative work behavior developed by Kleysen & Street (2001). The technique used in the data analysis process is using a simple linear regression test. The results of the study revealed that transformational leadership had a significant effect on innovative work behavior (R2 = 0.557, Sig. = 0.000). This shows that the influence of transformational leadership is able to explain 55.7% of innovative work behavior in baristas in Malang City.